Online Marketing Strategy Analysis of PT. Bagus Trans Wisata - Lesmana, Kevin Benedict; Marta, Rustono Farady; Wahjudi, Sugeng (E-Journal of Tourism; Volume 8 Number 1 (March 2021)DO - 10.24922/eot.v8i1.70278, 2021)
The tourism industry is one of the largest industries in the world, including Indonesia. So it is said that this industry has a considerable influence, so that it can be ascertained that this is an opportunity for a business. The large number of existing social media makes marketers have to see an appropriate and broad target. Based on this, marketers must be fully prepared with the selection of media, certain efforts and ways to attract consumers. PT. Bagus Trans Wisata has used new media as a channel in promoting its travel products. One of the new media used, namely Facebook, the use of this new media is one proof of the success of a well-known company name throughout Indonesia. New media is a new form of social media used by the public, considering that conventional media is less effective in conveying mass messages. This paper aims to examine marketing strategies through social media at PT. Bagus Trans Wisata. This research uses descriptive research with a qualitative approach which aims to identify, describe and explain the actual situation related to the marketing strategy undertaken by the service company PT. Bagus Trans Wisata Tour & Travel Jakarta. Keywords: online, marketing, tourism, travel